Persepsi Dosen Universitas PTIQ Jakarta - Dzulfatah Yasin (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This research aims to analyze the views of students from the College of Quranic Sciences (PTIQ) in Jakarta regarding polygamy in the context of religion and culture in Indonesia. The study adopts a qualitative approach by conducting a literature review and interviews with students from the mentioned college. The analysis reveals two dominant perspectives, those who support and those who reject polygamy. Some students perceive polygamy as a legitimate option within the teachings of Islam and specific contexts, while others reject it on the grounds of gender equality and the protection of women's rights. Moreover, the understanding of polygamy is also influenced by cultural factors, social environments, and personal experiences of the students. This research contributes to the existing literature on the views towards polygamy in Indonesia and aligns with previous studies that show how social, cultural, and religious factors influence perspectives on polygamy. In conclusion, students from the College of Quranic Sciences (PTIQ) in Jakarta hold complex views on polygamy within the framework of religion and culture in Indonesia. In addressing such a sensitive issue, a holistic approach is necessary to comprehend the factors influencing attitudes and perspectives towards polygamy. The findings of this research are expected to provide new insights and a deeper understanding of the dynamics of views on polygamy, serving as a foundation for further discussions within the realms of religion, culture, and society in Indonesia.